Interaction of Board Capital on Dividend Pay-Out and Financial Performance of Firms listed at Nairobi Securities Exchange in Kenya - Kurere, Cornelius; Limo, Patrick; Tenai, Joel (African Journal of Education,Science and Technology (AJEST), 2021)
The variations in financial performances of Kenyan firms registered at Nairobi Securities Exchange are dependent on the decision made by the board of directors more so on capital structure while from the previous studies there has been inadequate linkage of board capital and financial performance with other themes. Firms listed in Kenya have financed their operation with more of equity as compared to debt. The purpose of this study was to establish the moderating role of board capital on the relationship between dividend payout and financial performance for the firms registered at Nairobi Securities Exchange Kenya. The study objectives were to examine the effect of dividend pay-out on the financial performance of registered firm at Nairobi Securities Exchange in Kenya and to establish whether board capital has an interactive relationship on dividend Pay-Out and financial performance. The study was informed by stewardship theory. The philosophical foundation underpinning the study was positivism and an explanatory research design. The target population comprised of all the 65 firms registered at NSE in Kenya using census sampling method. However, all the suspended and delisted firms were excluded. As a result, panel data from audited financial reports were collected from 40 firms for a period of ten years 2008 to 2017. A data sample of 400 was therefore obtained from firms listed. Data was analyzed using Descriptive statistics; Mean median standard deviation, skewness and kurtosis while inferential statistics used were multiple regression analysis and Pearson correlation. In addition, panel regression analysis was engaged to establish the nature as well as significance of the association between dividend payout and financial performance. The outcome displayed that dividend pay-out had a negative influence on financial performance. The study findings are in contrast with the assertion that high dividends increase value with dividend pay-out (β= -.203, ρ<.05) to financial performance. Later the process was repeated with the moderating variable results showing that board capital has a negative and significant moderating influence on the association between dividend pay-out and financial/monetary performance (R2∆=0.05 β= -0.08; ρ<0.05). The study found that the board capital had a buffering moderation influence/impact on dividend pay-out on financial performance. Theoretically, the retention of dividends by the firms listed in NSE validates the stewardship theory, which is on the premise that managers as well as directors are honest and upright stewards of the resources assigned to them. Besides, though dividend pay-outs are construed to transmit information about the future profitability of firms, the study findings elicited a negative connection between dividend pay-outs and monetary performance. Similarly, when moderated with board capital, dividend pay-outs still negatively impacted on the financial performance. Overall, the findings are in line with theories that deem dividend pay-outs as irrelevant in enhancing financial performance. Finally, the researcher recommends a further study focusing on firms not listed in NSE to ascertain whether the study results hold.